2019
DOI: 10.1103/physrevb.100.064105
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced formation of rhodium zigzag chains in the honeycomb rhodateLi2RhO3

Abstract: We use powder x-ray diffraction to study the effect of pressure on the crystal structure of the honeycomb rhodate Li2RhO3. We observe low-pressure (P Pc2 = 14 GPa) regions corresponding to the monoclinic C2/m symmetry, while a phase mixture is observed at intermediate pressures. At P >Pc2, the honeycomb structure becomes distorted and features short Rh-Rh bonds forming zigzag chains stretched along the crystallographic a direction. This is in contrast to dimerized patterns… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…We find that SOC mainly brings the structure further to approximate C 3 symmetry of the honeycomb planes. This effect is in line with other studies of honeycomb ruthenates, iridates and rhodates [73][74][75] and consistent with the approximately C 3 -symmetric magnetic response observed in α-RuCl 3 [11,[76][77][78]. These observations also vindicate our work with a C 3 -simplified version of the obtained magnetic model throughout the discussions in the main text.…”
Section: Further Details Of First-principles Calculationssupporting
confidence: 92%
“…We find that SOC mainly brings the structure further to approximate C 3 symmetry of the honeycomb planes. This effect is in line with other studies of honeycomb ruthenates, iridates and rhodates [73][74][75] and consistent with the approximately C 3 -symmetric magnetic response observed in α-RuCl 3 [11,[76][77][78]. These observations also vindicate our work with a C 3 -simplified version of the obtained magnetic model throughout the discussions in the main text.…”
Section: Further Details Of First-principles Calculationssupporting
confidence: 92%
“…Several promising candidates with such layered honeycomb structure have since been investigated: Na 2 IrO 3 [3][4][5], α-Li 2 IrO 3 (as also its threedimensional polymorphs) [6,7], and α-RuCl 3 [8,9]. However, it has been revealed that these materials order magnetically [9][10][11][12][13][14][15] due to the presence of Heisenberg and other non-Kitaev terms, and the fingerprint of the Kitaev interactions may only be realized either at higher temperatures or under application of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Moreover, Li2RhO3 undergoes a structural distortion under elevated external pressure resulting in the formation of short Rh-Rh bonds building zigzag chains along the crystallographic a direction. 14 To the best of our knowledge, there is no information in the literature regarding compositions between layered LiRhO2 and Li2RhO3, and the role of Li for the phase formation. Since LiRhO2 of the NaCrS2 type transforms into the tunnel-like γ-MnO2 type rutile-ramsdellite intergrowth structure upon delithiation, which has never been seen for other layered transition metal oxides with alkali metals, further studies about parameters influencing this exotic transformation would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…The lithium or rhodium oxides known from the literature adopt crystal structures related to rock salt: LiRhO 2 of the layered NaCrS 2 type, spinel-like LiRhO 2 , or layered, Li-rich compounds of the Li 2 MnO 3 type with a honeycomb-like ordering of Li and Rh atoms. , Moreover, Li 2 RhO 3 undergoes structural distortion under elevated external pressure, resulting in the formation of short Rh–Rh bonds building zigzag chains along the crystallographic a direction …”
Section: Introductionmentioning
confidence: 99%